Registration and billing system - Chin Yong, Tan (2005)
Hospital Information System (HIS) is a new term for the system that is used to manage hospital activities. Inside the HIS there got so many modules such as In-Patient Module, Out-Patient Module,Radiology Module and others modules.A study has been done on a few of the existing system,such as Medinous - Hospital Management System, C-DAC's Sushrut - Hospital Information System (HIS) and File-Maker System. Some of the problems from the existing systems are like stand alone system,the system is not in the webbased format, the application has to be installed into every computer in the hospital or office, and others problems. To over come these problems,a Registration and Billing System Prototype have been developed.The format of the system prototype is a web-based application.The purpose of this development is to solve the existing problems found in the existing system.A software development process called Rapid Software Development Life Cycle(RSDLC) has been used to develop this system prototype.The purpose of using this software development process is to shorten the time for the software development process.The tools of the software development are Macromedia Dreamweaver MX 6.0; the JSP web dynamic programming language and Oracle 9i as the system database.The Registration and Billing System Prototype uses an integrated system database to store the patient data. To view the patient data and records, the bubble sort sorting algorithm has been applied.By applying this algorithm into the system prototype,the user of the system can get easily to look for the patient records in a list.